Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which value of [tex]\( x \)[/tex] is a solution to the equation [tex]\((x-2)(x+5) = 18\)[/tex], we will substitute each given value for [tex]\( x \)[/tex] and check if the equation holds true.
1. Checking [tex]\( x = -10 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-10-2)(-10+5) = (-12)(-5) = 60 \][/tex]
Since [tex]\( 60 \ne 18 \)[/tex], [tex]\( x = -10 \)[/tex] is not a solution.
2. Checking [tex]\( x = -7 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-7-2)(-7+5) = (-9)(-2) = 18 \][/tex]
Since [tex]\( 18 = 18 \)[/tex], [tex]\( x = -7 \)[/tex] is a solution.
3. Checking [tex]\( x = -4 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-4-2)(-4+5) = (-6)(1) = -6 \][/tex]
Since [tex]\( -6 \ne 18 \)[/tex], [tex]\( x = -4 \)[/tex] is not a solution.
4. Checking [tex]\( x = -2 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-2-2)(-2+5) = (-4)(3) = -12 \][/tex]
Since [tex]\( -12 \ne 18 \)[/tex], [tex]\( x = -2 \)[/tex] is not a solution.
Based on these calculations, the solution to the equation [tex]\((x-2)(x+5) = 18\)[/tex] is [tex]\( x = -7 \)[/tex].
1. Checking [tex]\( x = -10 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-10-2)(-10+5) = (-12)(-5) = 60 \][/tex]
Since [tex]\( 60 \ne 18 \)[/tex], [tex]\( x = -10 \)[/tex] is not a solution.
2. Checking [tex]\( x = -7 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-7-2)(-7+5) = (-9)(-2) = 18 \][/tex]
Since [tex]\( 18 = 18 \)[/tex], [tex]\( x = -7 \)[/tex] is a solution.
3. Checking [tex]\( x = -4 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-4-2)(-4+5) = (-6)(1) = -6 \][/tex]
Since [tex]\( -6 \ne 18 \)[/tex], [tex]\( x = -4 \)[/tex] is not a solution.
4. Checking [tex]\( x = -2 \)[/tex]:
[tex]\[ (x-2)(x+5) = 18 \implies (-2-2)(-2+5) = (-4)(3) = -12 \][/tex]
Since [tex]\( -12 \ne 18 \)[/tex], [tex]\( x = -2 \)[/tex] is not a solution.
Based on these calculations, the solution to the equation [tex]\((x-2)(x+5) = 18\)[/tex] is [tex]\( x = -7 \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.